Air Solar Flat Plate Collector analysis with induced Turbulence - Bagga, Gagandeep Singh (My University, 2016)
The most rustic application which could be used to exploit sun’s free energy bombarded on earth annually which is 15000 (aboltins et al. 2009) times more than the whole world’s industrial energy requirement is the solar air heater to pre-heat air for further drying, heating, lithe delicate parts and many more purposes. The solar air heaters performance rely on collector’s material, absorber and its orientation in the collector, air velocity in the collector (Lauva et al. 2006; Palabinskis et al. 2008), passage given to air flow as single pass or double pass air flow or multi-pass flow (Forson, Nazha, and Rajakaruna. 2003) and weather conditions. This report ponders over the various design parameters considered while designing the experimental set-up along with the effects of these parameters on performance of solar air collector. Two different convection modes were analysed namely; Natural mode and Forced convection mode to contemplate over the heat transfer coefficient associated with each case. Double glass as top cover is used to minimize losses pertaining to radiation. To reduce shading losses glass itself is used to make air flow through multi passes. CFD modelling is applied to predict the temperature pattern of air with radiation model DTRM and k-ἐ turbulence model. The setup works at an atmospheric pressure of 1.013N/m2 . The modelling gives good results when compared experimentally with natural convection mode. The temperature characteristics of air are plotted in the report comparing it with both convection modes. Artificial roughening of absorber unit is crucial to increasing heat transfer rates to air (Anil singh Yadav et al. 2014) and is done in the passages taken by air. Twisted wires is used which would set the air in the vicinity into circular motion analogous to swirling of fuel in internal combustion engines. It has been found that number of passages increases residence time of air and heat transfer to air, although increases pressure loss. The shading losses are compensated with glass partitions. Peak efficiencies are achieved on a sunny day from 12 noon to 2 pm
Keywords: solar collector; glass cover turbulence; solar drying